Utilization of the Local Wisdom of the South Aceh Community 'Peutron Aneuk' as a Biology Learning Resource in High Schools - Najira Ira; Siti Sriyati (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2025)
Local wisdom, such as the Peutron Aneuk tradition practiced in Southern Aceh, represents a valuable national asset and potential learning resource. This research explores the Peutron Aneuk tradition to identify its potential applications within biology education. By employing a qualitative methodology, specifically a literature review combined with interviews of local traditional elders, this study investigates the cultural significance and practical applications of Peutron Aneuk. The findings illustrate how elements of this tradition can be integrated into biology curricula, offering a culturally relevant and engaging approach to learning. The results highlight the relevance of Peutron Aneuk to various biological concepts, particularly biodiversity. This study contributes to understanding how local wisdom can enrich and enhance educational practices